ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS PESERTA DIDIK KELAS IX SMP NEGERI 1 SULIKI MENGGUNAKAN WATSON-GLASER CRITICAL THINKING APPRAISAL - Khairani Fuad Fatardha (Jurnal Edukasi dan Penelitian Matematika, 2020)
Critical Thinking skill is one that must be developed in mathematics lessons. However, the ability to think critically is less of a concern in learning. There is a test that is widely used to measure students' critical thinking skills, namely the Watson-Glaser Critical Thinking Appraisal (WGCTA). The research objective was to describe the level of critical thinking skills of students based on the WGCTA indicator. This type of research is a descriptive study with a qualitative approach. The research subjects were students of class IX-1 who were selected based on consideration. Instruments in the form of test questions and new interviews. The data obtained are the results of critical skills tests and interviews. The analysis techniques used include data reduction, data presentation and withdrawal. The technique to guarantee the validity of the data used is technical triangulation. Based on the results of the analysis and triangulation, it can show that students' critical thinking skills are generally in the medium category, except for the indicators analyzing argument which are in the low category.Keyword – analisis, critical thinking skills, Watson-Glaser Critical Thinking Appraisal